Exploring The Effect Of State-Owned Enterprise Corporate Social Responsibility On Small Medium Enterprise Digitalization In Indonesia - Akram Arsyad Sukma; Robith Hudaya; Tri Hanani (Cita Konsultindo Research Center, 2024)
This paper aims to investigate the role of state-owned enterprise (SOE) corporate social responsibility (CSR) program on the small medium enterprise digitalization in Indonesia. This research emphasizes measuring the implementation of SME digitalization with 3 main indicators, namely the use of e-commerce, social media and websites. Meanwhile, the company's corporate social responsibility is measured by five main programs, namely: coaching, marketing, financing, partnerships and availability of coworking space. The sample consist of 270 small medium enterprise that follow the program of stated owned enterprise corporate social responsibility during 2020 until 2023. The results reveal that the presence of state-owned enterprises CSR program especially financing and coworking space availability positively influence the small medium entreprise digitalization. On the other hand, this research has not been able to capture the significant impact of other State-Owned Enterprise CSR programs, such as coaching, financing, marketing and partnership on SME digitalization. This study extend the exploration of state-owned enterprise CSR program impact especially on SME digitalization. The findings of this research support decision makers and SOE-CSR managers in determining priority CSR programs that are empirically proven to support the success of SME digitalization. Finally, this study demonstrate how SOE-CSR improve SME digitalization